Applying the model of experience economy and intimacy to the sustainable development of culinary tourism of Majapahit Indigenous Food in Indonesia - Hendra Hendra; Hera Oktadiana; Sundring Pantja Djati; Myrza Rahmanita; I Dewa Gde Satrya; Adrie Octavio (Enrichment : Journal of Management, 2023)
Indigenous food can be seen as a catalyst for the goal of developing sustainable tourism. Indigenous food is increasingly being used as an integral part of visitor attraction to enrich their tourism experience, one of which is Majapahit indigenous food. Thus, correlating Majapahit indigenous food can create sustainable culinary tourism in Indonesia. This study aimed to explore the role of Majapahit indigenous food as culinary tourism in Indonesia by integrating two theories of consumer behavior, namely the Experience Economy and Intimacy Model. The data collection was carried out through a series of interviews with five informants involving historians, culinary entrepreneurs, tour and travel industry players, academician and tourists. The results showed that Majapahit indigenous food did not yet have strong competitiveness. As a result, the contribution made by Majapahit indigenous food to the development of sustainable culinary tourism seemed insignificant. Various suggestions and recommendations were also presented so that Majapahit indigenous food can be strongly integrated into the tourist experience.